(untitled) (Materiali di Estetica. Terza serie, 2022)
Rather than discussing beauty or ugliness as metaphysical categories I do prefer here to consider individual artistic worlds, and to defend the values in which I recognise myself as reader and enjoyer, in the various ways in which this can be articulated. Worlds in which aesthetic positivity and negativity are in tension, each resolving this dialectic in its own way. That’s why my paper doesn’t analyse Beauty or Ugliness tout-court. I do rather consider their dialectical intertwining and reflecting in specific works of art: The Idiot by Dostoevskij, the librettos to Wagner’s Lohengrin and Verdi’s Rigoletto, as well as Fatelessness by Imre Kertész. I intend to show how a negative experience can be transfigured in the structure and language of these writers and musicians.